Cognitive requirements for effective use of brain-computer interfaces (BCIs) in pediatric populations: A scoping review. - Rios Ortegon, Johana; Leung, Ada W. S.; Adams, Kim (Technology & Disability, 2025)
Background: Brain-computer interfaces (BCIs) are technologies that may allow children to operate assistive devices by translating their brain signals into commands for the devices. BCI technology requires specific user skills for successful operation. However, the cognitive demands remain relatively unexplored, particularly in pediatric populations, where developmental differences and cognitive variability significantly influence usability and performance. Objective: This review explores what has been reported on the cognitive requirements for using BCIs, with a focus on the pediatric population. Methods: A systematic search was conducted across six databases (Scopus, Web of Science, Embase, MEDLINE, PsycINFO, and CINAHL) for original research studies involving children aged 5–18 using BCIs for control purposes. Inclusion criteria focused on studies reporting cognitive factors relevant to BCI performance. Data extraction and analysis followed the PRISMA-ScR guidelines. Results: Seven studies met the inclusion criteria, highlighting attention, motivation, and processing speed as key factors influencing BCI performance. However, the limited pediatric research suggests significant gaps in understanding the cognitive factors involved in BCI performance. Conclusions: Further research is necessary to tailor BCI systems implementation to the unique cognitive and developmental needs of children. Addressing these gaps will enhance BCI usability and effectiveness, promoting greater independence for children with motor disabilities.